Neologi Istilah Politik Dalam Bahasa Arab Modern Kajian Morfologi - Aini, Nurul (ARABIYATUNA : Jurnal Bahasa Arab, 2018)
This study aims to determine the forms and rules of formation of political terms in Arabic language examined from the morphological aspects. This type of research is literature research. Data collection using direct observation method. Data analysis using top down method of distribution technique and data presentation using informal method. The results of this study show the form of political terms in Arabic consists of the form of words and phrases. The word form consists of nouns and verbs, either in the basic form of the word or affixation. The form of phrase consists of tarkib idhafi, verbal phrases, nominal phrases, jarr majrur and tarkib wasfi. The rule formation of Arabic political terms viewed from the morphological aspect consists of: a) the derivation of masdar, isim fā'il, isim maf'ūl, isim makān b) absorption, c) translation.